(untitled) (Ciudades, 2017)
Spatial centrality is generally associated to objective parameters: prime location, spatial quality, accumulation of activity and services, connectivity and functions as flowattraction node… There is also a more symbolic component related to the type of urban experience generated by a particular environment. The poetic vision of the most insubstantial sites of the city, defended by the first avant-garde movements of the twentieth century, helps to track the potential and future alternatives of a downtown currently dominated by market forces and the practice of leisure consumption as outstanding aim.